Multicenter study to describe viral etiologies, clinical profiles, and outcomes of hospitalized children with severe acute respiratory infections, Egypt 2022 - Kandeel, Amr; Fahim, Manal; Deghedy, Ola; H. Roshdy, Wael; K. Khalifa, Mohamed; El Shesheny, Rabeh; Kandeil, Ahmed; Wagdy, Saly; Naguib, Amel; Afifi, Salma; Abdelghaffar, Khaled (Scientific reports, 2023)
In late 2022, severe acute respiratory infections (SARI) surveillance reported an abrupt increase in non-COVID-19 infections among children after three years of drastic reductions. Signals of increased absenteeism due to respiratory symptoms among primary and preparatory school children were detected by Event-Based Surveillance. We conducted a hospital-based survey of children who were admitted with SARI to identify the causative pathogen(s) and estimate the burden of infection. A survey was conducted among children < 16 years in 21 referral hospitals in the three governorates with the highest SARI rates. Patients’ demographics, clinical symptoms, and severity were collected from medical records using a line list. Patients were swabbed and tested for a panel of 33 respiratory pathogens by RT-PCR at the Central Laboratory in Cairo. Descriptive data analysis was performed for demographic data. Patients’ characteristics were compared by causative agents’ clinical picture and severity using Chi2 with a p < 0.05 significance. Overall, 317 patients were enrolled, 58.3% were ≤ 1 year of age, 61.5% were males. Of 229 (72.7%) of positively tested patients, viruses caused 92.1% including RSV 63.8%, Rhinovirus 10.0%, Influenza 9.2%, Adenovirus 5.2%, and 1.3% co-infected with two viruses. Bacteria caused 3.5% of cases and 4.4% had mixed viral-bacterial infections. Rhinovirus was the most common cause of death among children with SARI, followed by RSV (8.7% and 1.4%), whereas influenza and Adenovirus did not result in any deaths. Patients with viral-bacterial infections are more likely to be admitted to ICU and die at the hospital than bacterial or viral infections (60% and 20% vs. 31.8% and 1.9% vs. 12.5% and 12.5%, p < 0.001). Viruses particularly RSV are the leading cause of SARI causing significant health problem among children < 16 years in Egypt. Bacterial on top of viral infection can worsen disease courses and outcomes. Studies are required to estimate the SARI burden accurately among Egyptian children and a comprehensive approach tailored to Egypt is necessary to reduce its burden.